ANALISIS CERITA RAKYAT JAKA TINGKIR: KAJIAN STRUKTURAL NARATIF VLADIMIR PROPP - Nur Rohmat Ardhika Putra; Sri Wahyuningtyas (CARAKA, 2017)
The aims of this study are. 1) To describe the function of the perpetrator. 2) To describe the distribution function of the perpetrator. 3) To describe the form of a theme of story. This type of research is qualitative research. The data used in this research is the primary data in form of a sentence or paragraph that describes the unit in the event Jaka Tingkir folklore. The data source is the text of folklore Jaka Tingkir Yuliadi Sukardi, U. Syahbudin. The instruments of this study is the researchers themselves who is assisted by a data card to record important words and supported by the Structural Narrative theory of Vladimir Propp. Data collection techniques in this study is the engineering literature. Data analysis technique used qualitative descriptive technique, that all data collected is recorded, identified, interpreted, and then results are described. The results of this study as follows. 1) There are 18 functions of the perpetrators among the 31 functions of the perpetrators, 18 of these functions is the initial situation (α), crime (A), cap (J), penalties (U), the first function of donor (D), mediation (B), the reaction of hero (E), a prescription from a shaman / paranormal (F), departure (↑), deceit (ƞ), displacement (G), struggle (H), victories (I), dissolution (K), the return (↓), heavy-duty (M), the solution (N), marriage (W). 2) There are five actors function that can’t be put into seven environmental action, namely: the return (↓), cap (J), dissolution (K), victories (I), and deceit (ƞ). 3) A schematic story is (α) A J U D B E F G H I ↑ ƞ K ↓ M N W. If constructed in the framework of the story, the shape of the scheme describes a movement which one to follow the movement of the other. A_________FM_____W*